2012
DOI: 10.1007/s11356-012-1366-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead and cadmium exposure from electronic waste on child physical growth

Abstract: Many studies indicate that lead (Pb) and cadmium (Cd) exposure may alter bone development through both direct and indirect mechanisms, increasing the risk of osteoporosis later in life. The aim of this study was to investigate the association between Pb and Cd exposure, physical growth, and bone and calcium metabolism in children of an electronic waste (e-waste) processing area. We recruited 246 children (3-8 years) in a kindergarten located in Guiyu, China. Blood lead levels (BLLs) and blood cadmium levels (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 42 publications
2
76
4
1
Order By: Relevance
“…The BCLs means were lower than those reported in 103 primary school children (6-12 years old) in Cairo city (1.34 μg/l) [59] and proved to be lower also in comparison with the means in French, Canadian an Chinese children living in urban areas (0.48 μg/l, 0.35 μg/l and 0.69 μg/l, respectively) [32,53,60], but they are somehow elevated in comparison with the BCLs means in children from many urban areas in Central Europe cities [28,[61][62][63][64].…”
Section: Blood Cadmiumcontrasting
confidence: 66%
See 1 more Smart Citation
“…The BCLs means were lower than those reported in 103 primary school children (6-12 years old) in Cairo city (1.34 μg/l) [59] and proved to be lower also in comparison with the means in French, Canadian an Chinese children living in urban areas (0.48 μg/l, 0.35 μg/l and 0.69 μg/l, respectively) [32,53,60], but they are somehow elevated in comparison with the BCLs means in children from many urban areas in Central Europe cities [28,[61][62][63][64].…”
Section: Blood Cadmiumcontrasting
confidence: 66%
“…Nevertheless, when we further analyzed the outcomes concerning BLLs effects on physical development of children, the only results found significant concerned girls from the urban area (N = 25) that had the highest BLLs mean in our population (89.451 μg/l) ( Table 1), and for whom BLLs were negatively correlated with height (r = -0.425, p = 0.034) and even negatively correlated with weight, but without clear significance (r = -0.369, p = 0.069). Yang et al (2012) [53] reported the same finding in Chinese children (3-8 years of age; BLLs mean: 73 μg/l) exposed to electronic waste. It has been known that lead affects negatively the physical development of children by blocking the absorption of calcium, iron and other elements, and inhibiting the synthesis and utilization of some hormones [54,55].…”
Section: Blood Cadmiummentioning
confidence: 62%
“…Metal mining and peat burning have already existed over several millennia in the British Isles (Mighall et al, 2002;Meharg and Killham, 2003;Oldfield et al, 2003), which could have resulted in trace element discharges directly in soil and emissions into the atmosphere which eventually deposit into soil. But the pre-industrial status of trace elements in soils is not obvious particularly in urban soils where the history of land use is complicated and thus the potential sources of contaminated soil are difficult to unravel (Leung et al 2008;Xu et al 2013aXu et al , 2013bYang et al, 2013a). Moreover, research into REEs in urban soils and the information on the impacts of REEs on human health are still lacking, especially the spatial distribution of REEs in topsoils.…”
Section: Introductionmentioning
confidence: 99%
“…The percentages of blood lead concentration exceeding 10 mg/dL in Guiyu children were 81.83% (2004) [2,16,17]. Cadmium levels in human and environmental samples from Guiyu are also higher than those in other places without e-waste recycling [7,[18][19][20][21]. Similar to the case of PBDEs, lead and cadmium may also relate to hormone alteration.…”
Section: Introductionmentioning
confidence: 90%